Cross-Calibrations of the HY-2B Altimeter Using Jason-3 Satellite During the Period of April 2019–September 2020 - Wang, Jianbo; Xu, Huan; Yang, Lei; Song, Qingjun; Ma, Chaofei (Frontiers in Earth Science, 2021)
In 2018, the Haiyang-2B (HY-2B) satellite altimeter was sent to orbit as a follow-up mission of the HY-2A satellite altimeter. The performance of the HY-2B system over the global oceans is considered to be critical. However, its performance is not fully known at the present time. In the present study, the first global quality assessment of the HY-2B Geophysical Data Record (GDR) was presented using comparison and crossover analysis processes of the main parameters and sea level anomalies (SLA) with Jason-3 GDR data. This study’s assessment results demonstrated that the editing proportion of unqualified data for the HY-2B was 2.67%, was at a similar level as the Jason-3 (2.86%). Also, this study’s assessment results of the HY-2B key parameters (mainly the backscatter coefficients, significant wave heights, sea state bias, wet troposphere delays, and ionosphere delays) showed good agreement with the Jason-3, and there were no abnormal trends observed. The mean and standard deviations (STD) were determined to be (0.21±6.70) cm and (-3.4±6.25) cm for the SLAs differences at the self-crossover points of the HY-2B and dual-crossover points between the HY-2B and Jason-3 satellites, respectively. In addition, the SLAs crossover analysis results indicated that the accuracy of the sea surface heights for the HY-2B were close to those of the Jason-3 satellite. The spatial distributions of the SLAs differences showed no significant errors in the geographic characteristics. The SLAs measurements were assessed using a wave-number spectra method. The obtained results suggested that the power spectrum of the SLAs of the HY-2B satellite followed the regular patterns of the traditional Jason-3 altimeter. Furthermore, based on the spectrum analysis results, it was revealed that the noise level of the HY-2B was lower than that of the Jason-3, indicating a good overall performance of the HY-2B.